Health Literacy and Occupational Therapy: A Discussion on Assessing and Addressing Limited Health Literacy - April M. Bryant; Bryan M. Gee; Lynn Gitlow (Scholarworks @ WMU, 2022)
Health literacy is multidimensional and goes beyond simply education level. In addition, age, gender, race and ethnicity, social network, and income level, among other things, can contribute to the level of health literacy and affect health outcomes. Many Americans cannot make sound decisions regarding their health care because of limited health literacy, yet health literacy is rarely considered during an occupational therapy evaluation and subsequent plan of care. This manuscript informs occupational therapists on strategies to address limited health literacy by using literature and evidence.